Request for outstanding amount and work completion certificate for piling and D-wall of BRAC University new campus project of the 13 storied institutional building - Next Spaces Limited (Brac University, 2023)
This record consists of general correspondence regarding request for outstanding amount and work completion certificate for piling and D-wall of BRAC University new campus project.